Current MSIS students' views on program outcomes - Topi, Heikki (2015)
This paper reports the results of a pilot survey sent to current specialized master's students in Information Systems at several universities around the world. The survey was developed to support the MSIS revision process, but the results will also provide insights on the perceptions of current IS master's students regarding their current degree program. The results suggest that the respondents valued individual foundational skills and high-level business competences more than technical or lower-level managerial competences. The study utilized competence specifications from the European e-CF 3.0 model, which was useful and performed well as a competence framework.